Identifikasi Perilaku Prokrastinasi Akademik Siswa SMA Swasta Kota Bengkulu - Jannah, Nurul; Ariani, Winda Ade; Sumarni, Ade Titin (JURNAL KONSELING GUSJIGANG, 2024)
The aim of the research is to identify students' academic procrastination behavior. Academic procrastination behavior can produce negative impacts, usually assignments are only started at the last minute of the submission deadline so that the work creates pressure, fear, anxiety, and has an impact on learning outcomes. Quantitative research method with a sample of 731 Bengkulu City Private High School students. Data collected using a questionnaire analyzed percentages. The results of the research show that academic procrastination behavior is in the form of delaying time to start and do assignments and doing other activities that are more enjoyable. As a student, you must be able to divide your time productively between studying and doing other enjoyable activities.